Diversity and Distribution Patterns of Gastropoda (Mollusca) in the Mangrove Area of Tiram Beach, Padang Pariaman Regency, West Sumatra Province - Remi Fiter; Syafruddin Nasution; Afrizal Tanjung (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
This study was conducted in March 2023 at Tiram Beach, Padang Pariaman Regency, West Sumatra Province. This study aims to determine the diversity and distribution patterns of gastropods in the mangrove area of Tiram Beach, Padang Pariaman Regency. The method used in this study was a survey method that involved direct observation of the study area, after which samples were analyzed in the laboratory. Gastropod sampling sites in the mangrove area were determined by targeted sampling consisting of 3 (three) stations at each station with three transects with 5 square plots of 1x1 m² spaced 10 m each. The results showed that the gastropod diversity in the Tiram Beach mangrove area was included in the low and medium categories. Gastropod distribution patterns at each station are categorized as clustered. Sediment organic matter in the Tiram Beach mangrove area achieved the highest average value of 4.52-22.13%. The sediment fraction at each station is silty sand and gravelly sand.